Correlates of current cigarette smoking among school-going adolescents in Punjab, India: results from the Global Youth Tobacco Survey 2003 - Rudatsikira Emmanuel; Muula Adamson S; Siziya Seter (BMC, 2008)
Abstract Background Smoking is a leading cause of morbidity and mortality globally. There is therefore need to identify relevant factors associated with smoking among adolescents in order to better tailor public health interventions aimed at preventing smoking. Methods We used data from the Global Youth Tobacco Survey (GYTS) conducted in 2003 in Punjab, India, on 2014 adolescents of whom 58.9% were males. We conducted a weighted logistic regression analysis, adjusting for age and sex, to determine associations between predictor variables and current tobacco smoking status. Results A total of 2014 adolescents participated in the survey in 2003, and of these 58.9% were males. Male respondents tended to be older than females (21.2% of males, and 13.1% of females were of age 16 years or above). The percent of males and females in the other age groups were: 23.0% and 28.6% for <14 years, 27.3% and 31.0% for 14 years, and 28.4% and 27.0% for 15 years, respectively. The following factors were positively associated with smoking: adolescents who received pocket money; adolescents who had parents who smoked, chewed or applied tobacco; adolescents who said that boys or girls who smoke or chew tobacco have more friends; adolescents who said that smoking or chewing tobacco makes boys look less attractive; adolescents who said that there is no difference in weight between smokers and non-smokers; adolescents who said that smoking makes one gain weight; and adolescents who had most or all of their closest friends who smoked. The factors that were negatively associated with smoking were: adolescents who said that boys or girls who smoke or chew tobacco have less number of friends; adolescents who said that girls who smoke or chew tobacco are less attractive; and adolescents who had some of their closest friends who smoked. Conclusion The observed associations between current smoking on one hand and peer smoking, and perception that boys who smoke are less attractive on the other, deserve further studies. The factors reported in the current study should be considered in the design of public health interventions aimed to reduce adolescent cigarette smoking.